PENGARUH JAMINAN SOSIAL DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWANBPR KARYA MURNI MENTENG MEDAN - Noni Noviana Saragih; Yuni Syahputri; Teddi Pribadi (Universitas Medan Area, 2020)
Employment is a very basic aspect of human life because it covers social and economic dimensions. One important objective in economic development is the provision of sufficient employment opportunities to pursue the growth of the workforce, which is growing faster than the growth of employment opportunities.Many approaches have been taken to manage human resources, one of which is by organizing social security programs. The social security provided by the company will provide employees with peace and security. The next thing that is also expected to affect one's performance at work is job training. With a high level of education and supported by job training, the workforce will have more opportunities to improve their performance.The Social Security variable has no significant effect on the performance of BPR Karya Murni Medan employees, as evidenced by the significance value of 0.492 0.05 and the t value of 0.689 t table 1.99045. Job Training has a significant influence on the performance of BPR Karya Murni Medan employees, as evidenced by the significance value of 0,00010.005 and the value of tcount 4.122 t table 1.99045. Social Security and Job Training simultaneously have a positive and significant effect on the Performance of BPR Karya Murni Medan employees, evidenced by a significance value of 0,0001 0.005 and F arithmetic 18,629 F table = 3.11.